2022
DOI: 10.14748/ssm.v54i2.8223
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and antimicrobial resistance of Staphylococcus spp. isolates associated with catheter-related bloodstream infections in patients after hematopoietic stem cell transplantation

Abstract: INTRODUCTION: The human body is colonized by a large number of different bacterial and fungal species, with most microorganisms inhabiting the skin, oral cavity, and the lower parts of the gastrointestinal tract. AIM: The aim of this study was to investigate the species diversity of clinically significant Staphylococcus spp. isolates, obtained from blood cultures of patients with central venous catheter (CVC) following hematopoietic stem cell transplantation (HSCT) during the period January 2019-December 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Our antibiotic susceptibility tests showed that CoNS was completely sensitive to vancomycin and linezolid, and slightly resistant to penicillin and aminoglycosides. This was somewhat different from what Niyazi D previously reported ( Niyazi et al., 2022 ): They found CoNS resistance rates to penicillin, erythromycin, gentamicin, and ciprofloxacin all exceeding 60%, significantly higher than our statistical results. We speculate that this may be caused by the high proportion of methicillin-resistant CoNS in their study cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Our antibiotic susceptibility tests showed that CoNS was completely sensitive to vancomycin and linezolid, and slightly resistant to penicillin and aminoglycosides. This was somewhat different from what Niyazi D previously reported ( Niyazi et al., 2022 ): They found CoNS resistance rates to penicillin, erythromycin, gentamicin, and ciprofloxacin all exceeding 60%, significantly higher than our statistical results. We speculate that this may be caused by the high proportion of methicillin-resistant CoNS in their study cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…In this issue of Scripta Scientifica Medica, Niyazi et al (1) analyzed a spectrum of clinically significant Staphylococcus spp. colonized central venous catheter (CVC) in the most immunosuppressed category of patients, those who have undergone hematopoietic cell transplantation (HCT) in myeloablative chemotherapyinduced aplasia, a reversible life threatened condition.…”
Section: Igor B Resnick MD Phd Dscmentioning
confidence: 99%